Iso-α-acids, Hop-Derived Bitter Components of Beer, Attenuate Age-Related Inflammation and Cognitive Decline - Ano, Yasuhisa; Ohya, Rena; Kondo, Keiji; Nakayama, Hiroyuki (Frontiers in Aging Neuroscience, 2019)
With the aging population rapidly increasing worldwide, preventive measures and treatments for age-related cognitive decline and dementia are of utmost importance. We have previously demonstrated that the consumption of iso-α-acids (IAA), which are hop-derived bitter compounds in beer, prevents the formation of disease pathology in a transgenic mouse model of Alzheimer’s disease (AD). However, the effect of IAA consumption on age-related cognitive decline is unknown. In the present study, we examined the effect of long-term and short-term dietary consumption of IAA, on age-related memory impairments and inflammation in the hippocampus of aged mice. When compared with young mice, aged mice showed impairment in spatial working memory during the Y-maze spontaneous alternation test, impairment in object recognition memory during the novel object recognition test (NORT), a pro-inflammatory hippocampal microglial phenotype with increased CD86 expression and inflammatory cytokine production, increased levels of glutamate and amyloid β1–42, and decreased levels of dopamine (DA). In aged mice fed IAA for 3 months, the age-related alterations in memory, microglial inflammation, and glutamate, amyloid β1–42, and DA levels were all significantly attenuated. Additionally, the oral administration of IAA for 7 days in aged mice with memory impairment, also improved spatial and object recognition memory. These results suggest that IAA consumption prevents inflammation in the hippocampus and ameliorates age-related cognitive decline.